The Influence of Certified Teacher Performance, Principal Supervision and Culture of Achievement on the Quality of MI Education in Sedan District, Rembang Regency. - Sadhikul Aziz Eka Matif; Fakhruddin, Fakhruddin; Mulyono, Sungkowo Edy (Universitas Negeri Semarang, 2024)
Teachers are one of the main factors determining the success of every educational endeavor. This can be studied from the teacher himself, including from the Performance of Certified Teachers, Principal Supervision, Culture of Achievement, and Quality of Education. Good productivity will be able to support the quality of education. To become a professional teacher and inseparable from the quality of education. However, in reality, the quality of teachers is still low, this is because the quality of education is still low below the KKM, which is 65 as evidenced by the results of the National Exam for students who are relatively low and fluctuate over the past 3 years. The population in this study is a school under the guidance of the Coordinator of the Sedan District Education Unit, Rembang Regency. The research sample in this study is 101 teachers using nonprobality sampling techniques with a saturated sampling type. This study uses quantitative. The data collection method is using a questionnaire. The data were analyzed using descriptive statistics, multiple linear regression analysis and assisted IBM SPSS. The results demonstrated that the Performance of Certified Teachers significantly and positively influences the Quality of Education. This finding highlights the critical role that effective and capable certified teachers play in enhancing educational outcomes through their professional performance. Similarly, Principal Supervision was shown to have a substantial positive impact on the Quality of Education, emphasizing the importance of strong leadership, guidance, and oversight in fostering an environment conducive to learning. Additionally, a robust Culture of Achievement contributes meaningfully to improving the Quality of Education, showcasing how shared values, aspirations, and commitment to success can enhance educational practices and outcomes